2015
DOI: 10.1161/circgenetics.115.001138
|View full text |Cite
|
Sign up to set email alerts
|

Superoxide Dismutase 1 In Vivo Ameliorates Maternal Diabetes Mellitus–Induced Apoptosis and Heart Defects Through Restoration of Impaired Wnt Signaling

Abstract: Background Oxidative stress is manifested in embryos exposed to maternal diabetes, yet specific mechanisms for diabetes-induced heart defects are not defined. Gene deletion of intermediates of Wingless-related integration (Wnt) signaling causes heart defects similar to those observed in embryos from diabetic pregnancies. We tested the hypothesis that diabetes-induced oxidative stress impairs Wnt signaling thereby causing heart defects, and that these defects can be rescued by transgenic overexpression of the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

4
6

Authors

Journals

citations
Cited by 57 publications
(60 citation statements)
references
References 51 publications
2
58
0
Order By: Relevance
“…Reduced cardiomyocyte proliferation and Cyclin D1 transcript expression was noticed in E13.5 embryos exposed to matDM (Supplemental Figure 9, A-J), which is either due to excess ROS production or the secondary effect of Notch1 downregulation in endocardial/endocardial-derived cells; however, the mechanism leading to VSD is beyond the scope of this study. It has been shown that overexpression of the superoxide dismutase (SOD) gene rescues CHD phenotypes in the offspring of mice with matDM but this may overexpression system may have numerous effects apart from decreased ROS (68). Similarly, NAC treatment of severely diabetic mice (average blood glucose >450 mg/dl) has been shown to partially rescue the CHD phenotypes (69).…”
Section: Discussionmentioning
confidence: 99%
“…Reduced cardiomyocyte proliferation and Cyclin D1 transcript expression was noticed in E13.5 embryos exposed to matDM (Supplemental Figure 9, A-J), which is either due to excess ROS production or the secondary effect of Notch1 downregulation in endocardial/endocardial-derived cells; however, the mechanism leading to VSD is beyond the scope of this study. It has been shown that overexpression of the superoxide dismutase (SOD) gene rescues CHD phenotypes in the offspring of mice with matDM but this may overexpression system may have numerous effects apart from decreased ROS (68). Similarly, NAC treatment of severely diabetic mice (average blood glucose >450 mg/dl) has been shown to partially rescue the CHD phenotypes (69).…”
Section: Discussionmentioning
confidence: 99%
“…Our recent studies demonstrated in the T1DM that impaired Wnt signaling and activation of the proapoptotic kinase apoptosis signal-regulating kinase 1 are involved in the induction of heart defects. 24,39 Future studies will reveal whether alterations of these signaling pathways contribute to the etiology of T2DM-induced heart defects.…”
Section: Commentmentioning
confidence: 99%
“…1,8,56 Although the efficacy of general antioxidants, including folic acid, in reducing adverse pregnancy outcomes is controversial, 7476 antioxidants with specific inhibitory effects on DNA methylation, such as Epigallocatechin gallate, may be better therapeutics.…”
Section: Commentmentioning
confidence: 99%